Basic Concepts of Evaluation In The Evaluation of Islamic Religious Education Learning In Schools - Ju'subaidi, Ju'subaidi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The notion of assessment in PAI learning in public elementary schools is the topic of discussion in this research. One of the most basic challenges facing the school system is, according to researchers, solvable. Due to the fact that evaluation is integrated into the many stages of learning, it has a crucial and strategic place within the learning process. The purpose of this analysis is to establish how successful and productive the educational system is. The assessment of learning programmes, procedures, and results are all included in the scope of this project. Continuity, comprehensiveness, fairness, objectivity, collaboration, and practicality are the main components that make up the assessment principles. Integration, coherence, pedagogy, and accountability are the specific components that make up the principles. Evaluations of learning may be broken down into many categories, including planning, development, monitoring, impact, and efficiency evaluations, as well as overall programme evaluations. The topic of learning assessment is one of them. This article will describe the fundamental idea of evaluation in the context of PAI learning in public elementary schools. In this particular research endeavour, a qualitative approach was used by gathering information in the form of words and images rather than numerical data. SD Negeri is where all of this research is being done. The PAI instructors, the school administrators, and the fifth-grade children attending state primary schools all participated as data sources for this research. In this research, the fundamental ideas of evaluation, as well as its roles and goals, evaluation processes and methodologies, PAI topics taught in primary schools, and the fundamentals of evaluation in PAI education, are discussed.